PENGELOLAAN LIMBAH KULIT KOPI MENJADI PRODUK TEH (CASCARA) BERNILAI TINGGI DI PERKEBUNAN KOPI RAKYAT KABUPATEN BANDUNG: PENGELOLAAN LIMBAH KULIT KOPI MENJADI PRODUK TEH (CASCARA) BERNILAI TINGGI DI PERKEBUNAN KOPI RAKYAT KABUPATEN BANDUNG - Maxiselly, Yudithia; Sari, Dwi Novanda; Bakti, Citra; Dewi Anjarsari, Intan Ratna (PT. RANESS MEDIA RANCAGE, 2023)
Mekarjaya Village, Banjaran District, Bandung Regency, is one of the best coffee producers in West Java. The location at the bottom of Mount Puntang makes this area dominated by coffee cultivation. The coffee bean production process also impacts the accumulation of coffee waste because half of the coffee cherries are mostly not used as a commercial products. Community service in the form of processing coffee skin waste is needed to deal with the problem of coffee waste and increase its added value. One derivative product that is starting to be in demand from coffee skins is coffee skin tea or cascara. Community service was implemented from January 2023 to March 2023 at the people's coffee farmers in Mekarjaya Village, Banjaran District, Bandung Regency. The method has several stages: area surveys, product demonstration plots, socialization, and evaluation. The regional survey results show that the area has great potential to process coffee waste as cascara. Based on the results of the pre-test, showed that coffee farmers did not know about cascara and its benefits. Meanwhile, after the socialization, the farmers understood and were interested in developing cascara products as one of the commercial uses of coffee waste. Keywords: Cascara, Banjaran, coffee farmer, waste.